The role of emotional and spiritual intelligence in enhancing teacher performance: A study of madrasah aliyah teachers - Nasrul, Nasrul; Hadiyanto, Hadiyanto; Jasrial, Jasrial; Anisah, Anisah (Indonesian Research Journal in Education |IRJE|, 2026)
This research aimed to explore the contributions of emotional intelligence and spiritual intelligence to the performance of Madrasah Aliyah teachers in Bukittinggi City. The study employed a quantitative correlational design, with a population of 191 teachers and a sample of 64 teachers selected using proportionate stratified random sampling. Data were collected using Likert-scale questionnaires measuring teacher performance, emotional intelligence, and spiritual intelligence. The instruments were tested for validity and reliability, and the data met the assumptions of normality, linearity, and non-multicollinearity. Data analysis employed multiple linear regression. The findings revealed that emotional intelligence contributed 57.4% to teacher performance, spiritual intelligence contributed 60.6%, and both variables together explained 70.4% of the variance, while other factors outside the model accounted for the remaining 29.6%. These results suggest that enhancing teachers' emotional and spiritual intelligence is crucial for improving their performance and should be incorporated into professional development programs for Madrasah Aliyah teachers in Bukittinggi City.